VALUE ADDED OF BIRD'S EYE CHILI (CAPSICUM FRUTESCENS L.): A CASE STUDY OF THE INTEGRATED VILLAGE ECONOMIC TRANSFORMATION PROGRAM IN GOLO ROPONG VILLAGE, WEST SATARMESE DISTRICT, MANGGARAI REGENCY - Suryani, Maria Karlina; Suek, Johanna; Bani, Aplonia; Adar, Damianus (Buletin Ilmiah Impas, 2025)
Bird's eye chili (Capsicum frutescens L.) is a horticultural commodity that plays an important role in influencing inflation and is classified as a leading commodity with high economic value. This study aimed to analyze the added value of bird's eye chili powder as part of the Integrated Village Economic Transformation Program (TEKAD) in Golo Ropong Village, West Satarmese District, Manggarai Regency. Specifically, this study identified the additional economic value generated by processing fresh chili into chili powder and evaluated its contribution to increasing the income of farmers and local business actors. Data were collected through direct observation, interviews, and questionnaires. The data were analyzed using the Hayami method, supported by calculations of labor days (HOK) and depreciation costs to obtain a comprehensive estimate of added value. The results show that the processing of bird's eye chili into chili powder generated positive added value. The added value from this processing reached IDR 236,630, indicating that converting fresh chili into powdered chili provided a significant increase in economic value. The value-added ratio was 48.75%, while profit from sales reached IDR 66.87, with a profit rate of 70.65%. These findings indicate that the TEKAD program has an important role in promoting village economic transformation through horticultural product processing, although farmers still face challenges in profit distribution and production facilities.